IMPROVING VOCABULARY ITEM MASTERY USING IMPROVISED SONGS IN 3rd GRADES STUDENTS OF MI DARUL HUDA CODO - budik, kusworo (Center for the Research and the Community Service, Islamic Institut of Hasanuddin Pare - Kediri, 2025)
This research used classroom action research. The research subjects were 3rd-grade students at MI Darul Huda Codo in the second semester of the 2023/2024 academic year, totaling 30 students. The results of the preliminary study show that there was a significant increase from cycle 1 to cycle 2, namely data on student learning outcomes and student behavior during the learning process. The study results show that the application of improvisational songs media was successful in increasing students' ability to learn English. The data analysis shows that the percentage of students' scores was above the researcher's success criteria, namely 75%, so it can be concluded that the use of a standardized vocabulary test was effective in improving students' English vocabulary.